Strategi Pemasaran Digital Produk UMKM di Kota Pasuruan dengan Aplikasi LINKTREE - Ermatry Hariani; Retno Febriyastuti Widyawati; Ardya Ayu Dewanti (Universitas Pahlawan Tuanku Tambusai, 2022)
Along with the increase in online business and technological advances that continue to grow, we must be able to carry out good strategies to increase the number of consumers. Our products on social media will be better known to many consumers if they can provide convenience for consumers to visit our sales website. This convenience can be done by using supporting applications, such as Linktree. Linktree is one of the recommended applications for loading multiple links in the Instagram Bio. In fact, in the field, there are still a few SMEs who use this application to increase their sales targets. With these problems, the purpose of this community service activity is to provide education to MSMEs in the Pasuruan city area. MSMEs need more education regarding their product marketing strategies in online business by using available supporting applications. The method used is Focus Group Discussion (FGD) via online. The result of this service: MSME actors are easier to evaluate their online marketing strategies so as to improve their skills and knowledge in developing digital marketing of their products.